Investigating Neurophysiological, Perceptual, and Cognitive Mechanisms in Misophonia - Chhayakanta Patro; Emma Wasko; Prashanth Prabhu; Nirmal Kumar Srinivasan (Biology)
Misophonia is a condition characterized by intense, involuntary distress or anger in response to specific sounds, often leading to irritation or aggression. While the condition is recognized for its emotional and behavioral impacts, little is known about its physiological and perceptual effects. The current study aimed to explore the physiological correlates and perceptual consequences of misophonia through a combination of electrophysiological, perceptual, and cognitive assessments. Seventeen individuals with misophonia and sixteen control participants without the condition were compared. Participants completed a comprehensive battery of tests, including (a) cortical event-related potentials (ERPs) to assess neural responses to standard and deviant auditory stimuli, (b) the spatial release from the speech-on-speech masking (SRM) paradigm to evaluate speech segregation in background noise, and (c) the flanker task to measure selective attention and cognitive control. The results revealed that individuals with misophonia exhibited significantly smaller mean peak amplitudes of the N1 and N2 components in response to oddball tones compared to controls. This suggests a potential underlying neurobiological deficit in misophonia patients, as these components are associated with early auditory processing. However, no significant differences between each group were observed in the P1 and P2 components regarding oddball tones or in any ERP components in response to standard tones. Despite these altered neural responses, the misophonia group did not show differences in hearing thresholds, speech perception abilities, or cognitive function compared to the controls. These findings suggest that while misophonia may involve distinct neurophysiological changes, particularly in early auditory processing, it does not necessarily lead to perceptual deficits in speech perception or cognitive function.